A large parathyroid adenoma presenting with pathological fractures in a young male - Sahu, P. K.; Galagali, J. R.; Singh, I. D.; Kumar, Satish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2015)
Parathyroid adenoma is the common cause of primary hyperparathyroidism and usually presents with features of hypercalcaemia. In the present case report, we describe a case of a large adenoma of the parathyroid gland presenting with pathological fractures. A 42 year old Male presented with bony pains and fracture of the left humerus after a trivial trauma. A detailed clinical examination and laboratory studies revealed hypercalcaemia secondary to hyperparathyroidism. The patient underwent targeted parathyroidectomy of the involved gland after appropriate preoperative localization. Histopathology of the resected specimen was consistent with parathyroid adenoma. Conclusion is a common cause of primary hyperparathyroidism is a common endocrine disorder occurring as a result of Parathyroid adenoma in 80-85% cases. Patients usually present with symptoms related to hypercalcaemia. A high index of suspicion, careful preoperative workup, localization of the affected gland(s) and surgical excision ensures a successful cure.